1969
DOI: 10.1139/v69-770
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of gases on 4A synthetic zeolite

Abstract: Equilibrium data are presented for the adsorption of permanent gases and C , and C z hydrocarbons on Linde 4A synthetic zeolite from 50 "C down to the boiling point of the adsorbate or to a temperature at which the rate was very slow. The Freundlich equation often fits isotherms accurately; however, these lincar logarithmic plots secnl to be only portions of a more general non-linear relationship. Generallzcd Polanyi plots did not yield a ilniquc characteristic curve for individual adsorbates at different temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…This is true also of the data of Springer (13), Cook (14), and Harper et al (15) for sorption of argon in both 4A and 5A zeolites.…”
Section: Argonsupporting
confidence: 72%
“…This is true also of the data of Springer (13), Cook (14), and Harper et al (15) for sorption of argon in both 4A and 5A zeolites.…”
Section: Argonsupporting
confidence: 72%
“…It is noted, however, that zeolite 4A is able to more preferably adsorb N 2 than O 2 . 21 The different adsorption capabilities and thus the adsorption affinity of zeolite A for these gases may be responsible for our observations. For the CO 2 / CH 4 pair, although CO 2 can be more adsorbed than CH 4 by zeolite 4A, its rather appreciated quadrupole is able to render it forming stronger interactions with the zeolite pore surface, and hence CO 2 molecules may be harder to leave the active sites and move forward.…”
Section: The Zeolite 4a/pes Mixed Matrix Membranesmentioning
confidence: 83%
“…A previous study [67] showed that quadrupolar molecules such as CO 2 and C 2 H 4 have a tendency to be adsorbed more in a zeolite particularly by the anisotropic interactions between the quadrupole moment of adsorbate and the metal cations in the host zeolite. Later studies by Yoon and Huh [28] demonstrated a C 2 H 4 encapsulation capacity of 1.54 molecule cavity À1 on a mixed cations zeolite A (40% K and 60% Na) at pressure of 36 MPa.…”
Section: Encapsulation Investigationmentioning
confidence: 98%